Abundance and distribution of radioactive cesium-rich microparticles released from the Fukushima Daiichi Nuclear Power Plant into the environment. (February 2020) - Ikehara, Ryohei; Morooka, Kazuya; Suetake, Mizuki; Komiya, Tatsuki; Kurihara, Eitaro; Takehara, Masato; Takami, Ryu; Kino, Chiaki; Horie, Kenji; Takehara, Mami; Yamasaki, Shinya; Ohnuki, Toshihiko; et al.
Abstract: The abundance and distribution of highly radioactive cesium-rich microparticles (CsMPs) that were released from the Fukushima Daiichi Nuclear Power Plant (FDNPP) during the first stage of the nuclear disaster in March 2011 are described for 20 surface soils collected around the FDNPP. Based on the spatial distribution of the numbers (particles/g) and radioactive fraction (RF) of the CsMPs in surface soil, which is defined as the sum of the CsMP radioactivity (in Bq) divided by the total radioactivity (in Bq) of the soil sample, three regions of particular interest have been identified: i. ) near-northwest (N-NW), ii. ) far-northwest (F-NW), and iii. ) southwest (SW). In these areas, the number and RF of CsMPs were determined to be 22.1–101 particles/g and 15.4–34.0%, 24.3–64.8 particles/g and 36.7–37.4%, and 0.869–8.00 particles/g and 27.6–80.2%, respectively. These distributions are consistent with the plume trajectories of material released from the FDNPP on March 14, 2011, in the late afternoon through to the late afternoon of March 15, 2011, indicating that the CsMPs formed only during this short period. Unit 3 is the most plausible source of the CsMPs at the beginning of the release based on an analysis of the sequence of release events. The lower RF values in the N-NW region indicate a larger influence from subsequent plumes that mainly consisted of soluble Cs species formed simultaneously with precipitation. The quantitative map of the distribution of CsMPs provides an important understanding of CsMP dispersion dynamics and can be used to assess risks in inhabited regions. Graphical abstract: Image 1 Highlights: The distribution of Cs-rich microparticles emitted from the FDNPP is determined. Cs-rich microparticles account for a significant fraction of FDNPP-deposited Cs. The timing and source of the Cs-rich microparticle formation has been estimated.